2022
DOI: 10.53730/ijhs.v6ns1.6438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silanization on shear bond strength between high translucency zirconia and resin cement

Abstract: Aim: This in-viro study aimed to evaluate and compare the shear bond strength of resin cement with high translucency zirconia with silane coupling agents and bonding agent separately (Group3), bonding agent containing silane (Group 2) and bonding agent which does not have silane (Group 1). Materials and Methods: The study was conducted by using the high translucency zirconia blanks along with the CAD-CAM equipments. After sintering the specimens according to manufacturer’s instructions surface modifications, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Few Studies [3,4,9,10,11] have found no difference in bond failures with Low Intensity LEDs over Halogen Light Cure Systems. Though SBS with use of High Intensity LEDs and Low Intensity LEDs were comparable [12,13,14] and significantly higher than clinically needed values, since using the former saves chair-side time and reduces chances of moisture contamination [5], the same are the best ones for clinical use.…”
Section: Methodology Flow Chartmentioning
confidence: 87%
“…Few Studies [3,4,9,10,11] have found no difference in bond failures with Low Intensity LEDs over Halogen Light Cure Systems. Though SBS with use of High Intensity LEDs and Low Intensity LEDs were comparable [12,13,14] and significantly higher than clinically needed values, since using the former saves chair-side time and reduces chances of moisture contamination [5], the same are the best ones for clinical use.…”
Section: Methodology Flow Chartmentioning
confidence: 87%